The epidemiology and outcomes of women with postpartum haemorrhage requiring massive transfusion with eight or more units of red cells: a national cross‐sectional study. (23rd December 2015) - Green, L; Knight, M; Seeney, FM; Hopkinson, C; Collins, PW; Collis, RE; Simpson, NAB; Weeks, A; Stanworth, SS
Abstract : Objective: To ascertain the incidence of massive transfusion (MT) in obstetrics in the UK, and describe its management and clinical outcomes. Design: A population‐based cross‐sectional study conducted through the UK Obstetric Surveillance System (UKOSS). Settings: All UK hospitals with consultant‐led maternity units. Population: Any pregnant woman at ≥20 weeks of gestation receiving ≥8 units of red blood cells within 24 hours of giving birth, from July 2012 to June 2013. Methods: Prospective case identification through the monthly mailing of UKOSS. Results: We identified 181 women who had undergone MT, making the estimated incidence of MT associated with postpartum haemorrhage (PPH) 23 per 100 000 maternities (95% confidence interval 19–26) per year. The median estimated blood loss was 6 l (interquartile range 4.5–8.0 l). The majority of women presented outside working hours (63%), 40% had had previous caesarean sections and 3% had normal vaginal births without risk factors. The main cause for MT was uterine atony (40%) and the main mode of birth was caesarean section (69%). Of the 181 women, 15 received >20 units of red blood cells. In total, 45% of women underwent hysterectomy, and among all causes of PPH, placenta accreta had the highest hysterectomy rate. Two women died, 82% were admitted to intensive care/high‐dependency units, and 28% developed major morbidities. Conclusion: Massive transfusion due to PPH is associated with high rates of morbidity and hysterectomy. Clinical and research efforts should focus on approaches to recognise and optimise timely resuscitation and management of these severe cases. Tweetable abstract: Massive transfusion due to postpartum haemorrhage is associated with high rates of morbidity and hysterectomy. Tweetable abstract: Massive transfusion due to postpartum haemorrhage is associated with high rates of morbidity and hysterectomy.